SISTEM PEWARISAN PADA MASYARAKAT BERKASTA KSATRIA DAN MASYARAKAT BERKASTA SUDRA DI DESA PAKRAMAN MANUABA, KECAMATAN TEGALLALANG, KABUPATEN GIANYAR - ARDANA, I MADE SUKA (Jurnal Pendidikan Kewarganegaraan Undiksha, 2013)
ABSTRACTThis recearch aims to know 1) heritage system of Ksatria caste and Sudra caste of people in Manuaba villlage; 2) the differences of heritage system between Ksatria caste and Sudra caste of people in Manuaba village; 3) implication toward heir in family life and society in Manuaba village. This research uses descriptive qualitative. In choosing subject, research uses purpostive sampling and the subject of research are 1) people who have Ksatria caste, 2) people who have Sudra caste,3) Kelihan Banjar, 4) Bendesa Adat, 5) doyen in Manuaba village. The research uses some methods in collecting data, such as: 1) interview method, 2) observation method, 3) documentation method. In analysing the data, the research uses descriptive qualitative method. The results of this research show that 1) heritage system in Manuaba village was taken from man’s clan or in Bali we called it as purusa, but there is a diference between Ksatria caste and Sudra caste in heritage system. In Ksatria caste, the heir is the oldiest son of the family and in contrast, in Sudra caste the heir is the youngest son of the family; 2) there is difference of heritage system in Manuaba village and it is used for differenciate Ksatria caste and Sudra caste; 3) The implication of heir in family life and society are the heir has responsibility toward their parents, the heir has power in the family, the heir has responsibility in the society (in Bali we called it as ayahan banjar) and village.Keywords : Heritage System, Ksatria Caste, Sudra Caste